Los beneficios seculares de la diócesis de Tlaxcala en 1591 - Viforcos Marinas, María Isabel (1999)
This article uses a relation of secular benefices subscribed by bishop Diego Romano in 1591 as its documentary base. This report and information prepared by the same prelate in 1582 is analyzed to take a first look at the secular clergy of Tlaxcala: their training, origins, and knowledge of indigenous languages at the end of the sixteenth century.
Keywords: Clero; Diócesis (Derecho canónico) -- Tlaxcala